Longitudinal clinico-serological analysis of anti-nucleocapsid and anti-receptor binding domain of spike protein antibodies against SARS-CoV-2. (November 2021) - Deshpande, Gururaj Rao; Kaduskar, Ojas; Deshpande, Ketki; Bhatt, Vaishali; Yadav, Pragya; Gurav, Yogesh; Potdar, Varsha; Khutwad, Kirti; Vidhate, Shankar; Salunke, Asha; Patil, Chetan; Shingade, Snehal; et al.
Highlights: Data on perseverance of antibody responses against SARS-CoV-2 is vital and scanty 608 samples collected from 284 symptomatic/asymptomatic COVID-19 positive patients Persistence of binding antibodies observed in > 75 % cases till 240 days POD Neutralizing antibody response was seen in 80% of cases till 240 days POD Severe disease was associated with higher SRBD IgG and NAb responses Abstract: Objectives: Monitoring the antibody responses to SARS-CoV-2 infection and its correlation to clinical spectrum of disease is critical in understanding the disease progression and protection against re-infection. We assessed the nucleocapsid (N) and receptor-binding-domain of spike (SRBD) protein specific IgG and neutralizing antibody (NAb) responses in COVID-19 patients up to 8 months and its correlation with diverse disease spectrum. Methods: During the first wave of the SARS-CoV-2 pandemic, from 284 COVID-19 patients, 608 samples were collected up to 8 months post infection. The patients were categorized as asymptomatic, symptomatic and severe. The N and SRBD IgG and NAb titers were evaluated and correlated with clinical data. Results: A steep increase in antigen specific antibody titers was observed till 40 days post onset of the disease (POD), followed by a partial decline till 240 days. Severe disease was associated with a stronger SRBD IgG response and higher NAb titers. The persistence of antibody response was observed in 76% against N, 80% against SRBD and 80% for NAbs of cases up to 8 months POD. Conclusion: RBD and N protein specific IgG persisted till 240 days POD which correlated with NAb response, irrespective of individual`s symptomatic status indicating overall robust protection against re-infection.